3rd Generation Biofuels Disruptive Technologies to Enable Commercial Production - Jacob-Lopes, Eduardo; Jacob-Lopes, Eduardo; Queiroz Zepka Phd, Leila; Severo, Ihana Aguiar (Woodhead Publishing, 2022)
3rd Generation Biofuels: Disruptive Technologies to Enable Commercial Production is a comprehensive volume on all aspects of algal biofuels, offering the latest advances on commercial implementation. In addition to the fundamentals, the book discusses all applied aspects of 3rd generation biofuels production, including design approaches, unit operations of the upstream and downstream biomass processing, and every potential microalgae-based energy product, including microbial fuel cells. Policy, economic, environmental, and regulatory issues are addressed in a dedicated section. Finally, the book presents pilot and demonstration-scale projects for 3rd generation biofuels production in the format of a white paper. Each chapter reviews the state of the art, discusses the disruptive technological approaches that will potentially enable large-scale production, and concludes with specific recommendations on how to achieve commercial competitiveness. The book provides readers with an invaluable reference for researchers, graduates, and practitioners working in the areas of renewable energy, bioenergy and alternative fuels, and biotechnology. - Offers a sequential framework for the design of process plants using 3rd generation feedstock - Presents dedicated sections on case studies at pilot and demonstration scales as well as on policy, economic, and environmental issues - Provides a global perspective on biofuels production, with more than 40 contributions from world-renouned experts